Integrating the Perceived Neighborhood Environment and the Theory of Planned Behavior When Predicting Walking in a Canadian Adult Sample - Rhodes, Ryan E.; Brown, Shane G.; McIntyre, Carolyn A. (American journal of health promotion, 2006)
Purpose. To integrate the characteristics of the perceived environment with the theory of planned behavior (TPB) to determine (1) whether the TPB mediates relations among environmental characteristics and walking, and (2) whether the environment moderates TPB-walking relations. Design. Cross-sectional. Setting. South Vancouver Island, British Columbia, Canada. Subjects. Random sample of 351 adults (36% response rate). Measures. Participants completed measures of the perceived neighborhood environment, the TPB, and walking behavior that was assessed using an adapted Godin leisure time questionnaire. Results. Results using structural equation modeling indicated that the TPB mediated the environment-walking relationship. Specifically, retail land-mix use and neighborhood aesthetics were associated with walking through affective and instrumental attitudes. Results using moderated regression analyses showed that recreation land-mix use moderated the intention-behavior relationship, with those individuals who perceived closer access to recreation facilities having a larger intention-behavior relationship. A significant moderating effect for crime on the instrumental attitude-intention relationship was also identified, but the effect size was small to trivial. Conclusions. These results suggest that the perceived neighborhood may influence walking through attitudes and may also influence the intention-behavior gap. Prospective studies using objective walking and environment data are required to improve the veracity of the findings and to identify possible causal relationships.